Clinical Features and Outcomes of Glutamic Acid Decarboxylase‐65 Antibody‐Associated Pure Cerebellar Ataxia and Stiff Person Syndrome Spectrum Disorders: A Single‐Center Cohort Study - Krett, Jonathan D.; Wang, Yujie; Miles, Ashley; Chen, Herbert R.; Afshar, Hanyeh; Elfasi, Aisha; Lin, Doris D.; Newsome, Scott D. (European journal of neurology, 2025)
ABSTRACT Background Cerebellar ataxia is associated with greater disability in glutamic acid decarboxylase‐65 (GAD65) antibody‐associated neurological disorders and can occur in isolation or as part of stiff person syndrome (SPS) spectrum disorders (SPSD). We sought to phenotypically characterize this subpopulation with cerebellar dysfunction. Methods Observational study of GAD65 antibody‐seropositive individuals with cerebellar involvement seen at Johns Hopkins (1997–2024). Subjects were divided into two groups based on cerebellar dysfunction in the presence (SPSD; SPS‐plus and progressive encephalomyelitis with rigidity and myoclonus [PERM]) or absence (pure cerebellar ataxia [pCA]) of classic SPS features. Clinical and paraclinical findings were analyzed descriptively. Results Seventy‐two patients were selected among 356 (62 SPSD, 10 pCA). Mean age for patients with pCA was 58 ± 16 years versus 46 ± 15 years for SPSD (p = 0.012). Males comprised 50% of the pCA group versus 19% SPSD (p = 0.049). High GAD65 antibody serum titers occurred in 76% without group differences, while cerebrospinal fluid antibody positivity occurred in 35/37 (95%) of SPSD versus 5/8 (62%) pCA (p = 0.033). Although the modified Rankin scale was similar (median 3, interquartile range 2–4) in both groups, the brief ataxia rating scale indicated a higher burden of cerebellar abnormalities in pCA versus SPSD, and there was a trend toward greater cerebellar atrophy by MRI in pCA (p = 0.44). Rituximab and benzodiazepine use was more frequent in SPSD versus pCA. Conclusions GAD65 antibody‐associated ataxia is disabling irrespective of accompanying SPS features. Patients with pCA were older, more commonly male, and may have more frequent cerebellar atrophy than those with SPSD. Prospective validation of cerebellar outcomes and neuroimaging findings is needed.